2015
DOI: 10.1371/journal.pone.0141225
|View full text |Cite
|
Sign up to set email alerts
|

A catalogue of novel bovine long noncoding RNA across 18 tissues

Abstract: Long non-coding RNA (lncRNA) have been implicated in diverse biological roles including gene regulation and genomic imprinting. Identifying lncRNA in bovine across many differing tissue would contribute to the current repertoire of bovine lncRNA, and help further improve our understanding of the evolutionary importance and constraints of these transcripts. Additionally, it could aid in identifying sites in the genome outside of protein coding genes where mutations could contribute to variation in complex trait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
86
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 53 publications
(101 reference statements)
7
86
3
Order By: Relevance
“…For example, Wang et al [33] reported 2805 lncRNA transcripts in the pig endometrium (using 12 porcine samples and 85–105 million reads per sample), and Billerey et al [34] reported approximately 1300 lncRNA transcripts in bovine muscle (using nine samples with 15 million to 45 million reads per sample). In contrast, multi-tissue studies reported a larger number of lncRNA transcripts, generally above 10,000, with a wide variation depending on the sequenced tissues and the tools used for the lncRNA detection (9778 lncRNA transcripts reported by Koufariotis et al [16] in 18 bovine tissues (using 1.87 million 120-bp stranded paired-end reads and CPC/CNCI tools for lncRNA prediction [24, 35]), and 20,163 lncRNA transcripts reported by Li et al [36] in 13 maize tissues (using 1.17 million 35- to 110-bp unstranded paired- and single-end reads and the CPC tool for lncRNA prediction [24]).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wang et al [33] reported 2805 lncRNA transcripts in the pig endometrium (using 12 porcine samples and 85–105 million reads per sample), and Billerey et al [34] reported approximately 1300 lncRNA transcripts in bovine muscle (using nine samples with 15 million to 45 million reads per sample). In contrast, multi-tissue studies reported a larger number of lncRNA transcripts, generally above 10,000, with a wide variation depending on the sequenced tissues and the tools used for the lncRNA detection (9778 lncRNA transcripts reported by Koufariotis et al [16] in 18 bovine tissues (using 1.87 million 120-bp stranded paired-end reads and CPC/CNCI tools for lncRNA prediction [24, 35]), and 20,163 lncRNA transcripts reported by Li et al [36] in 13 maize tissues (using 1.17 million 35- to 110-bp unstranded paired- and single-end reads and the CPC tool for lncRNA prediction [24]).…”
Section: Resultsmentioning
confidence: 99%
“…Given that approximately 80% of the variants associated with human complex traits map outside of protein-coding exons of which 40% are in intergenic regions [12, 13], identifying the lncRNA repertoire is crucial to better understand the “genotype to phenotype” relationships in livestock [14, 15]. To date, few lncRNA studies have been reported for livestock species, apart from lncRNA studies in bovine [16] and trout [17], and the construction of multi-species databases such as NONCODE [18, 19] and the domestic-animal lncRNA database (ALDB) [20, 21]. Research programs are in progress on several farm species, e.g., in projects conducted within the framework of the Functional Annotation of Animal Genomes initiative [14, 15].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Billerey et al [132] characterized 584 lncRNAs in bovine muscle in addition to significant correlated expression between 2083 pairs of lncRNA/protein encoding genes. Koufariotis et al [133] [136] identified 1336 specific lncRNAs in fetal skin of Youzhou dark goat (dark skin) and Yudong white goat (white skin). Similarly, Chao et al [137] in a study with aim to identify and classify new transcripts in Dorper and small-tail Han sheep muscle transcriptomes predicted with high confidence 1520 transcripts to be lncRNAs.…”
Section: Long Non-coding Rna In Mammary Gland Development and Lactatimentioning
confidence: 99%
“…Particular considerations for lncRNA transcript construction include sample pooling according to species and tissue type. LncRNA expression is known to demonstrate tissue speciicity [66][67][68].…”
Section: Transcript Construction and Quantiicationmentioning
confidence: 99%